Increasing The Effectiveness of Islamic Religious Education Learning in Building Students’s Spiritual Intelligence - Jadid Khadavi; Ahmat Nizar; Akhmad Syahri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Effective Islamic Religious Education learning will motivate students to excel and have high spiritual values. With high spirituality, integrity will be built by involving inner unity and more dynamic social relations, as well as the ability of individuals to have a life orientation that is far into the future. This research is field research conducted at Madrasah Aliyah al-Khoiriyah Probolinggo. Data collection techniques were carried out through interviews, observation, and documentation. The research subjects included school principals, deputy heads of curriculum, deputy heads of student affairs, Islamic religious education teachers, and students. Data analysis techniques with data triangulation consist of data collection, data reduction, data presentation, and conclusion. The results of the study show that: First, the institution's efforts in building the spiritual intelligence of Madrasah Aliyah al-Khoiriyah Probolinggo students, namely applying time discipline in terms of Duha prayer activities and Teaching and Learning Activities (KBM); Second, increasing the learning of Islamic Religious Education (PAI) in building spiritual intelligence is carried out through inculcating Islamic values ​​and noble morals which are embodied in all learning activities and exemplary teachers in schools.